PENGARUH MODEL DISCOVERY LEARNING TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN TEKNOLOGI INFORMASI DAN KOMUNIKASI - Faridatus Sholeha (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2022)
The ability of students in the learning process learning motivation is still low, this can be seen from the lack of active students in the learning process because there is a sense of boredom, boredom and lack of enthusiasm in participating in learning. on ICT subjects for class XI IPS MA Raudhatus Shalihin. This study uses quantitative methods, the approach used is the ex post facto approach. The research sample determination technique uses purposive sampling, while the sampling technique uses a saturated sample technique. So the sample used is class XI MA Raudhatus Shalihin with a total of 28 respondents. The data collection technique uses a questionnaire in the form of a statement to be filled in by the respondent. Data analysis using t test using manual formula. It can be seen from the results of the t-test, it is known that the value of tcount = 4.272 and the value of ttable = 2.048 means tcount> ttable. With that, it can be concluded that there is an effect of the Discovery Learning model on students' learning motivation in ICT subjects for class XI at MA Raudhatus Shalihin